2004
DOI: 10.1093/bioinformatics/bth234
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression network topology provides a framework for molecular characterization of cellular state

Abstract: Software implementing the methods for network generation presented in this paper is available for academic use by request from the authors in the form of compiled linux binary executables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
263
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(268 citation statements)
references
References 21 publications
3
263
0
2
Order By: Relevance
“…A distance measure commonly used for coexpression analysis is based on the Pearson's coefficient of correlation; in this approach, gene pairs with a coefficient of correlation below a given cutoff value (e.g., 0.8) are considered as not correlated. However, this kind of "hard thresholding" may be insensitive to subtle and yet important expression patterns (85). We therefore used the WGCNA method (33,34), which uses a "soft thresholding" and the concept of topological overlap or shared neighbors to identify clusters of coexpressed genes.…”
Section: Methodsmentioning
confidence: 99%
“…A distance measure commonly used for coexpression analysis is based on the Pearson's coefficient of correlation; in this approach, gene pairs with a coefficient of correlation below a given cutoff value (e.g., 0.8) are considered as not correlated. However, this kind of "hard thresholding" may be insensitive to subtle and yet important expression patterns (85). We therefore used the WGCNA method (33,34), which uses a "soft thresholding" and the concept of topological overlap or shared neighbors to identify clusters of coexpressed genes.…”
Section: Methodsmentioning
confidence: 99%
“…We tested whether the commonly used coexpression method (Carter et al, 2004) generates a network similar to that of Figure 4 (see Supplemental Methods 1 online). We found that 75% of Arabidopsis GSN edges are different from those found in the corresponding coexpression network, supporting our conclusion (Figure 2) that GSN and coexpression networks capture different properties of the expression data (see Discussion).…”
Section: Arabidopsis Gsnmentioning
confidence: 99%
“…This basic molecular mechanism leads naturally toward a network view of transcription in which individual genes serve as nodes connected by edges to other genes (Lee et al, 2002). Transcriptional networks can be constructed from microarray data based upon co-expression analysis (Carter et al, 2004;Rice et al, 2005;Wolfe et al, 2005;Wang et al, 2006;Freeman et al, 2007;Huttenhower et al, 2007). Co-expression analysis connects genes within a network when the correlation between their expression profiles exceeds a certain threshold.…”
Section: Introductionmentioning
confidence: 99%